2011
DOI: 10.1182/blood-2010-12-323162
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells control HIV replication in activated T cells through a cAMP-dependent mechanism

Abstract: We hypothesized that regulatory T cells (Tregs) could play a beneficial role during HIV infection by controlling HIV replication in conventional T cells (Tcons). Purified Tregs and Tcons from healthy donors were activated separately. Tcons were infected with the X4 or R5 HIV strains and cultured with or without autologous Tregs. Coculture of Tcons and Tregs resulted in a dose-dependent inhibition of Tcon infection, which was significant when a 1:1 Treg:Tcon ratio was used. Treg suppression of HIV infection was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 51 publications
3
99
0
1
Order By: Relevance
“…In fact, cytotoxic activity of CD4 ϩ T cells against human pathogens has been described mainly for chronic viral infections (36 ϩ T cells have been described (48). In HIV infection, a cyclic AMP (cAMP)-dependent mechanism involving the enzyme CD39 was recently described (49). This effect requires cell-to-cell contact, which is in line with data from in vitro Treg suppression assays in the FV model (50).…”
Section: Fig 5 Fv Loads After T Cell Depletion Splenocytes From Diffsupporting
confidence: 69%
“…In fact, cytotoxic activity of CD4 ϩ T cells against human pathogens has been described mainly for chronic viral infections (36 ϩ T cells have been described (48). In HIV infection, a cyclic AMP (cAMP)-dependent mechanism involving the enzyme CD39 was recently described (49). This effect requires cell-to-cell contact, which is in line with data from in vitro Treg suppression assays in the FV model (50).…”
Section: Fig 5 Fv Loads After T Cell Depletion Splenocytes From Diffsupporting
confidence: 69%
“…Furthermore, Favre et al recently postulated that in gut-associated lymphoid tissue (GALT), expansion of Treg in response to inflammation may support disease progression by preventing the recovery of Th17 cells, resulting in persistent mucosal barrier dysfunction and failure to clear translocated microbial products (31). However, other reports have suggested that Treg play a largely beneficial role, either by suppressing HIV-replication in conventional CD4 ϩ cells (66) or by limiting nonspecific immune activation (17,51). Indeed, because immune activation closely correlates with disease progression (19,40,63,88), it is possible that in the context of chronic infection the beneficial aspects of the Treg response outweigh the disadvantages.…”
mentioning
confidence: 94%
“…In vitro, Tregs were shown to directly control HIV infection in susceptible targets, such as macrophages infected by a pseudotyped HIV (51) or infected conventional T cells (58), thus providing a potential mechanism for the correlative studies described above. In particular, we showed that cAMP was critical for this antiviral effect, acting either by direct transfer of cAMP through gap junctions or by the extracellular pathway, which involves CD39 activity (58).…”
Section: The Bright Side Of Tregs In Hiv Infection: the Antiviral Effectmentioning
confidence: 99%